2012
DOI: 10.1111/j.1540-6210.2011.02483.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Administrative Reform in New Democracies

Abstract: Practitioners and scholars of postcommunist politics disagree on the accomplishments of administrative reforms in new Eastern European democracies. The transformation of the public sector after 1989 has aimed to consolidate the democratic process and enhance economic development. Skeptics, however, argue that administrative reforms face serious challenges in the context of economic liberalization, insufficient capacity for modernization, and cultural legacies of the past. The authors judge reform effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 49 publications
4
66
0
3
Order By: Relevance
“…While conceptions of government transparency and their study focuses are diverse, government transparency encompasses policy-making transparency, openness of political process and public service programs priority transparency [10,15,26,30]. Specifically, an empirical research on the effects of public service reform found that the institution's act of adopting administrative reform by itself produced the beneficial impact on government transparency in new Eastern European democracies [21]. Survey studies in East Central Europe explained variation in local government transparency as a function of the institutions, as opposed to socioeconomic development or locality size [8].…”
Section: Government Transparencymentioning
confidence: 99%
“…While conceptions of government transparency and their study focuses are diverse, government transparency encompasses policy-making transparency, openness of political process and public service programs priority transparency [10,15,26,30]. Specifically, an empirical research on the effects of public service reform found that the institution's act of adopting administrative reform by itself produced the beneficial impact on government transparency in new Eastern European democracies [21]. Survey studies in East Central Europe explained variation in local government transparency as a function of the institutions, as opposed to socioeconomic development or locality size [8].…”
Section: Government Transparencymentioning
confidence: 99%
“…Dunn et al 2006;Neshkova and Kostadinova 2012;Dan and Pollitt 2014) at the level of individuals, organisations and systems. Th erefore, we predict that the EU-13 and (potential) candidate countries that embraced more wide-ranging reforms in the form of long-term strategies but have weaker implementation capacities are more likely to suff er from diffi culties in the process of reform delivery compared to the EU-15 and EFTA countries.…”
Section: H2: More Wide-ranging Reforms Are Likely To Face Greater Impmentioning
confidence: 99%
“…A ello contribuirá, el impulso de instrumentos para la supervisión de los proyectos y contratos, así como, el fortalecimiento del control del desempeño, la evaluación y la audi-toría de las acciones objeto de colaboración. Una gestión transparente contribuye a la lucha contra la corrupción y atraerá inversión (Neshkova y Kostadinova, 2012). c) Elaboración de decisiones colaborativas.…”
Section: Condiciones Del Contexto Político Administrativo Y Situacionalunclassified